2013
DOI: 10.1097/shk.0b013e318281a58c
|View full text |Cite
|
Sign up to set email alerts
|

Rattus Model Utilizing Selective Pulmonary Ischemia Induces Bronchiolitis Obliterans Organizing Pneumonia

Abstract: Background Bronchiolitis obliterans organizing pneumonia (BOOP), a morbid condition when associated with lung transplant and chronic lung disease, is believed to be a complication of ischemia. Our goal was to develop a simple and reliable model of lung ischemia in the Sprague-Dawley rat that would produce BOOP. Methods Unilateral ischemia without airway occlusion was produced by an occlusive slipknot placed around the left main pulmonary artery. Studies were performed 7 days later. Relative pulmonary and sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…We have reported that unilateral ischemia of the lung induced by pulmonary artery tie results in bronchiolitis obliterans organizing pneumonia (BOOP) and inflammatory changes seven days after surgery in SD rats (6). To begin to test the contribution of A 2B AR expression to the development of BOOP, we quantified percent BOOP in ischemic lungs of a genetically modified rat strain with deletions of A 2B AR relative to the background strain (Dahl SS)(22).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have reported that unilateral ischemia of the lung induced by pulmonary artery tie results in bronchiolitis obliterans organizing pneumonia (BOOP) and inflammatory changes seven days after surgery in SD rats (6). To begin to test the contribution of A 2B AR expression to the development of BOOP, we quantified percent BOOP in ischemic lungs of a genetically modified rat strain with deletions of A 2B AR relative to the background strain (Dahl SS)(22).…”
Section: Resultsmentioning
confidence: 99%
“…Four-micron thick slices of paraffin-embedded, fixed whole-mount coronal sections of left and right lung were stained for hematoxylin and eosin. Extent of bronchiolitis obliterans organizing pneumonia (BOOP) was quantified by assessing percentage of the cross sectional area of the lung involved at low power, morphology confirmed with high resolution JPEG images, as we previously reported (6). Histology consistent with BOOP (Masson bodies, inflammation, and young fibroblasts filling the distal airways and alveoli) was assessed with high power images.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations